Is subscapularis repair associated with better outcome compared to non-repair in reverse total shoulder arthroplasty? A systematic review of comparative trials - Malahias, Michael-Alexander (Orthop Rev (Pavia), 2019)
We aimed to investigate whether combined reverse total shoulder arthroplasty (RTSA) and subscapularis repair leads to improved clinical and functional outcome in comparison with RTSA alone. Two reviewers independently conducted a systematic search according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) using the MEDLINE/PubMed database and the Cochrane Database of Systematic Reviews. These databases were queried with the terms “reverse” AND “shoulder” AND “arthroplasty” AND “with” AND “subscapularis” AND “repair”. From the 72 initial studies, we finally chose five studies which were eligible to our inclusion-exclusion criteria. The total mean modified Coleman methodology test was 55/100 (range: 47/100 to 60/100). The eligible studies included 1087 patients, in total. Regarding the subjective functional scores as well as range of motion (ROM), the differences amongst groups were insignificant in almost all studies. The mean complications’ rate of the repair group was 10.4%, whereas the respective rate of the nonrepair group was 10.2%. All studies concluded that the repair of subscapularis did not affect the complications’ rate of patients who were treated with RTSA. The mean dislocations’ rates of the repair and the nonrepair group were 1.5% and 2.3%, respectively. Although subscapularis repair was proven safe and effective for the augmentation of RTSA, it did not offer any additional clinical or functional benefit in the outcome of patients treated with lateralized RTSA. Therefore, it is not supported its routine use for patients who have a preoperatively sufficient subscapularis tendon.